INTERPRETASI SEJARAH SEBAGAI PERISTIWA DAN MASALAH PENDIDIKAN - Ahmad Maksum (AT-TURATS, 2015)
When we talk about history, we usually think of the past and interpret it as something insignificant that does not need to be remembered at all. People merely know the events on the surface, but are not aware of the background. For historians and observers of history, an event must be explained further and more in-depth especially about how it happened, as well as social, economic, political, and cultural backgrounds. Simply recounting an event does not completely explain it, because historians are professional travelers in the world of the past. In the academic context, history is a field of science or study that requires a critical historical imagination in its analysis. This is intended to place history in its phenomenological setting. History is not only about the “past events”, but it is also related to current events. The role of historians is very strategic especially in changing society’s idea which should start from the concept of learning at school or college. In this light, historians and history teachers should be able to see through the mind of historical actors by trying to revive the thoughts of the historical actors in his/her own mind; in other words, historians should be able to put themselves into the shoes of the actors in history. It is considered an essential element in the “historical thinking” which serves as the basis of historical explanation. History as an autonomous discipline needs to be developed in accordance with the pattern of the tendency of history itself. Conventional historical writing only tells the story of history in a descriptive-narrative form, simply explaining how an event occurs and does not touch its focal point. To get a more complete picture of the reality, people need to approach historical events from various aspects better known as a multidimensional approach, and it certainly requires a method called an interdisciplinary method.